We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
77
1
avatar

-100 * 2^(0.5y) = -5

Which of the following is the solution of the equation?

 Apr 24, 2019
 #1
avatar+101870 
+1

-100 * 2^(0.5y)  = -5   divide both sides by -100

 

2^(0.5y)  =  -5/-100  = 1/20    take the log of both sides

 

log 2^(0.5y)  = log (1/20)      and we can write

 

(0.5y) * log 2  = log (1/20)

 

y  =  log(1/20) / (0.5* log 2 ]

 

y = (1/0.5) *  log (1/20) / log 2         reverse the change-of-base theorem

 

y =  2  * log2  (1/20)

 

 

cool cool cool

 Apr 24, 2019

8 Online Users

avatar